pH-Controlled Release of Antigens Using Mesoporous Silica Nanoparticles Delivery System for Developing a Fish Oral Vaccine - Zhang, Weibin; Zhu, Chunhua; Xiao, Fangnan; Liu, Xiaodong; Xie, Anhua; Chen, Fangman; Dong, Panpan; Lin, Pingdong; Zheng, Chenyang; Zhang, Hong; Gong, Hui; Wu, Yunkun (Frontiers in Immunology, 2021)
The development of effective vaccines and delivery systems in aquaculture is a long-term challenge for controlling emerging and reemerging infections. Cost-efficient and advanced nanoparticle vaccines are of tremendous applicability in prevention of infectious diseases of fish. In this study, dihydrolipoamide dehydrogenase (DLDH) antigens of Vibrio alginolyticus were encapsulated into mesoporous silica nanoparticles (MSN) to compose the vaccine delivery system. Hydroxypropyl methylcellulose phthalate (HP55) was coated to provide protection of immunogen. The morphology, loading capacity, acid-base triggered release were characterized and the toxicity of nanoparticle vaccine was determined in vitro. Further, the vaccine immune effects were evaluated in large yellow croaker via oral administration. In vitro studies confirmed that the antigen could be stable in enzymes-rich artificial gastric fluid and released under artificial intestinal fluid environment. In vitro cytotoxicity assessment demonstrated the vaccines within 120 μg/mL have good biocompatibility for large yellow croaker kidney cells. Our data confirmed that the nanoparticle vaccine in vivo could elicit innate and adaptive immune response, and provide good protection against Vibrio alginolyticus challenge. The MSN delivery system prepared may be a potential candidate carrier for fish vaccine via oral administration feeding. Further, we provide theoretical basis for developing convenient, high-performance and cost-efficient vaccine against infectious diseases in aquaculture